Corneal Stem Cells as a Source of Regenerative Cell-Based Therapy - Jasmin S. Nurković; Radiša Vojinović; Zana Dolićanin (Stem Cells International)
In the past few years, intensive research has focused on corneal stem cells as an unlimited source for cell-based therapy in regenerative ophthalmology. Today, it is known that the cornea has at least two types of stem cells: limbal epithelial stem cells (LESCs) and corneal stromal stem cells (CSSCs). LESCs are used for regeneration of corneal surface, while CSSCs are used for regeneration of corneal stroma. Until now, various approaches and methods for isolation of LESCs and CSSCs and their successful transplantation have been described and tested in several preclinical studies and clinical trials. This review describes in detail phenotypic characteristics of LESCs and CSSCs and discusses their therapeutic potential in corneal regeneration. Since efficient and safe corneal stem cell-based therapy is still a challenging issue that requires continuous cooperation between researchers, clinicians, and patients, this review addresses the important limitations and suggests possible strategies for improvement of corneal stem cell-based therapy.